2020
DOI: 10.3389/fped.2020.00431
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Children With COVID-19: A Meta-Analysis

Abstract: Background: With the global spread of novel coronavirus disease 2019 (COVID-19), health care systems are facing formidable challenges. Scientists are conducting studies to explore this new disease, and numerous studies have been shared. However, the number of studies on children with COVID-19 is limited, and no meta-analysis of this group has been performed. Methods: A random-effect meta-analysis was conducted to determine the characteristics of children with COVID-19, including their demographic, epidemiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
145
5
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(185 citation statements)
references
References 42 publications
27
145
5
8
Order By: Relevance
“…presymptomatic (6)(7)(8)(9). Prearrival testing with timely results, strict quarantining, and NPI use during transit were important, as was conscientious NPI use in the first 2 weeks after arrival.…”
Section: Resultsmentioning
confidence: 99%
“…presymptomatic (6)(7)(8)(9). Prearrival testing with timely results, strict quarantining, and NPI use during transit were important, as was conscientious NPI use in the first 2 weeks after arrival.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, various studies have reported that children are likely to have a higher proportion of asymptomatic infection than adults. However, the largest meta-analysis and systematic review studies to date report that only approximately 17%-27.7% of confirmed pediatric cases are asymptomatic (37,38). As with the adult population, the accuracy of this reported data remains unclear, as there are significant concerns regarding potential selection bias and testing error.…”
Section: Clinical Featuresmentioning
confidence: 96%
“…For this reason, most of the guidelines published so far are more appropriate for adults than for children. Several systematic reviews with simple meta-analysis have been reported, but these have mainly focused on the clinical characteristics of pediatric COVID-19 (5)(6)(7), and data on the transmissibility, rate of viral coinfections, and treatments of pediatric COVID-19 are still lacking. Asymptomatic transmission is the Achilles' heel of COVID-19 pandemic control, as reported by Gandhi et al (8), but the number of asymptomatic infections in children is unknown.…”
Section: Introductionmentioning
confidence: 99%